Pantoprazole in the management of dyspepsia in diabetic gastroparesis: evaluating efficacy and safety - Saha, Bibhuti; Behera, Sanjay; Dash, Nrusingha; Rao, Sreenivasa; Mittal, Subhash (International Journal of Advances in Medicine, 2025)
Background: Pantoprazole is used in treatment of erosive esophagitis associated with gastroesophageal reflux disease (GERD). This questionnaire-based study aims to provide insights into pantoprazole’s real-world effectiveness and safety in managing dyspepsia due to diabetic gastroparesis (DGP). Methods: This questionnaire-based study was conducted among Indian healthcare professionals (HCP) from September 2024 to March 2025. A questionnaire comprising 13 questions explored preferences of HCPs for use of pantoprazole in last 10 patients with dyspepsia due to diabetic gastroparesis. Results: A total of 86 HCP were included in this study. The highest percentage of HCPs (30.23%) reported duration of diabetes in patients greater than 10 years with age group of patients 40-60 years. A majority of 89.53% HCPs reported GERD, with abdominal discomfort reported by 38.37% of HCPs. Symptoms like post-prandial fullness and early satiety was observed at frequency of 6/10 patients by 38.37% HCPs, while poor glycemic control at a frequency of 5/10 patients by 38.37% of HCPs. Majority of 59.30% HCPs prescribed pantoprazole treatment for 4 weeks and 95.35% of HCPs added a prokinetic to pantoprazole. The largest proportion of HCPs (43.02%) reported symptom relief in 8/10 patients with 48.84% of HCPs observed glycemic control improvement in <8 patients. Loose stools were the most commonly reported adverse effect by 70.93% of HCPs. Approximately 90% of HCPs rated pantoprazole’s efficacy, safety and adherence to treatment as excellent and good. Conclusion: This study revealed strong clinical, therapeutic, and patient-centric outcomes across India for use of pantoprazole in patients with dyspepsia due to DGP.